Brain development is altered in rabbit fetuses with congenital diaphragmatic hernia. (1st February 2023) - Van der Veeken, Lennart; Russo, Francesca Maria; Bleeser, Tom; Basurto, David; Emam, Doaa; Regin, Yannick; Gsell, Willy; Himmelreich, Uwe; De Catte, Luc; Rex, Steffen; Deprest, Jan
Abstract: Introduction: Children with congenital diaphragmatic hernia (CDH) are at risk for neurodevelopmental delay. Some changes are already present prenatally. Herein,  we further examined how the brain develops in fetal rabbits with surgically created DH. Methods: Two fetuses underwent surgical DH creation on day 23 (term = d31). DH pups and littermate controls were harvested at term. Ten DH pups and 11 controls underwent transcardial perfusion for brain fixation and measurement of brain volume, brain folding, neuron and synaptic density, pre‐oligodendrocyte count, proliferation, and vascularization. Twelve other DH and 11 controls had echocardiographic assessment of cardiac output and aortic and cerebral blood flow, magnetic resonance imaging (9.4 T) for cerebral volumetry, and molecular assessment of vascularization markers. Results: DH pups had lower lung‐to‐body weight ratio (1.3 ± 0.3 vs. 2.4 ± 0.3%; p  < 0.0001) and lower heart‐to‐body weight ratio (0.007 ± 0.001 vs. 0.009 ± 0.001; p  = 0.0006) but comparable body weight and brain‐to‐body weight ratio. DH pups had a lower left ventricular ejection fraction, aortic and cerebral blood flow (39 ± 8 vs. 54 ± 15 mm/beat; p  = 0.03) as compared to controls but similar left cardiac ventricular morphology. Fetal DH‐brains were similar in volume but the cerebellum was less folded (perimeter/surface area: 25.5 ± 1.5 vs. 26.8 ± 1.2; p  = 0.049). Furthermore, DH brains had a thinner cortex (143 ± 9 vs. 156 ± 13 μm; p  = 0.02). Neuron densities in the white matter were higher in DH fetuses (124 ± 18 vs. 104 ± 14; p  = 0.01) with comparable proliferation rates. Pre‐oligodendrocyte count was lower, coinciding with the lower endothelial cell count. Conclusion: Rabbits with DH had altered brain development compared to controls prenatally, indicating that brain development is already altered prenatally in CDH. Key points: What's already known about this topic? Children with congenital diaphragmatic hernia (CDH) are at increased risk for neurodevelopmental delay. Prenatal changes have been described on fetal MRI and ultrasound; however, the extent and the pathogenesis of these changes are still controversial. It is unknown if this is a result of postnatal events or if this is already present prenatally. What does this study add? This study demonstrates that in CDH brain development is already altered prenatally. This study also demonstrates how changes in blood circulation can lead to abnormal brain development.